2017
DOI: 10.1111/pan.13302
|View full text |Cite|
|
Sign up to set email alerts
|

The pharmacokinetics of intravenous ketorolac in children aged 2 months to 16 years: A population analysis

Abstract: Clearance, expressed as L h kg , decreased with age from infancy. A dosing regimen of 0.5 mg kg every 6 hours maintains a trough concentration larger than 0.37 mg L in children 9 months to 16 years of age. This dosing regimen is consistent with current recommendations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
0
6
0
1
Order By: Relevance
“…Ketorolac is recovered in the urine mainly in its metabolite form. When intravenous ketorolac PK were studied in children aged 2 months to 16 years, it was found that from infancy CL decreased with age [ 50 ]. This study concluded that a dose of 0.5 mg/kg every 6 h was sufficient to keep trough concentrations above 0.37 mg/L, which produced sufficient analgesia postoperatively.…”
Section: Pharmacokinetics Of Non-steroidal Anti-inflammatory Drugs (N...mentioning
confidence: 99%
“…Ketorolac is recovered in the urine mainly in its metabolite form. When intravenous ketorolac PK were studied in children aged 2 months to 16 years, it was found that from infancy CL decreased with age [ 50 ]. This study concluded that a dose of 0.5 mg/kg every 6 h was sufficient to keep trough concentrations above 0.37 mg/L, which produced sufficient analgesia postoperatively.…”
Section: Pharmacokinetics Of Non-steroidal Anti-inflammatory Drugs (N...mentioning
confidence: 99%
“…Esto es discutible ya que, al menos con el uso de paracetamol, las presentaciones endovenosas no son más efectivas que las orales y el costo es más elevado [2]. Con respecto a ketorolaco, éste es ampliamente usado en niños (0,5 mg/Kg/dosis) [10] sin embargo, no está aprobado por la FDA. Una revisión sistemática Cochrane 2018, muestra que no hay evidencia suficiente para recomendar su uso, ni tampoco para evaluar su seguridad [11].…”
Section: Dolor Posoperatorio En Cirugía Ambulatoria Pediátricaunclassified
“…In the article by McLay et al in Volume 28 Issue 2 of Pediatric Anesthesia, the penultimate author Ahmed F. Hawwa was inadvertently omitted.…”
Section: The Pharmacokinetics Of Intravenous Ketorolac In Children Agmentioning
confidence: 99%